2014
DOI: 10.1158/1078-0432.ccr-13-2364
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Bevacizumab in Children with Osteosarcoma: Implications for Dosing

Abstract: Purpose To describe sources of interindividual variability in bevacizumab disposition in pediatric patients and explore associations among bevacizumab pharmacokinetics and clinical wound healing outcomes. Experimental Design Prior to tumor resection, three doses of bevacizumab (15 mg/kg) were administered to patients (median age 12.2 years) enrolled on a multi-institutional osteosarcoma trial. Serial sampling for bevacizumab pharmacokinetics was obtained from 27 patients. A population pharmacokinetic model w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 37 publications
5
38
0
2
Order By: Relevance
“…A novel finding from the present study that we previously reported is that bevacizumab exposure (i.e., area under the concentration-time curve, AUC) prior to surgery was associated with increased risk of major wound healing complications after surgery. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel finding from the present study that we previously reported is that bevacizumab exposure (i.e., area under the concentration-time curve, AUC) prior to surgery was associated with increased risk of major wound healing complications after surgery. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The sampling strategy, sample analysis, and development of the population pharmacokinetic model for bevacizumab have been previously described. 22 Bevacizumab concentration-time data were fit to a two-compartment model with first order elimination from the central compartment. Bevacizumab exposure [area under curve (AUC)] from the first dose (week 0) to time of methotrexate administration was estimated for each patient using a nonlinear mixed effects model in NONMEM (version 7.3; ICON solutions, Hanover, MD), a software package utilized for population pharmacokinetic modeling.…”
Section: Methodsmentioning
confidence: 99%
“…In the present retrospective cohort, the prognostic significance of serum CRP level in patients with osteosarcoma was successfully identified. For those osteosarcoma patients with high serum CRP level, more adjuvant treatments may be necessary and can be added to improve the survival [4,5,14].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Norway showed that there was no improvement in the overall survival for osteosarcoma since the 1990s, and the survival rates were still poor for elderly people or patients with metastatic diseases [2]. Previous studies have suggested that patients with poor histological response to chemotherapy or advanced stages usually have worse prognosis [4][5][6]. It is no doubt that identification of prognostic factors to choose starting and reasonable therapy is very helpful to improve patients' survival.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, FcRn expression was suggested to be increased with inflammation, which would lead to an decrease in mAb intrinsic clearance. [4] Elimination half-life (T½R) estimates of bevacizumab was 21 days in teleangiectasia [147] , 17-20 days in various solid tumours [148,149] , 15-17 days in child sarcoma [144,150] , and 19 days in colorectal cancer (CRC) and, surprisingly, 44 days in multi-metastatic CRC. [130] For trastuzumab, T½R was 28 days in metastatic breast cancer (BC), but highly controversial in early BC, 12 days [94] or 40 days.…”
Section: Influence Of Diseasementioning
confidence: 99%